STRATEGI COUNTERINSURGENCY KOLOMBIA TERHADAP FARC (FUERZAS ARMADAS REVOLUCIONARIAS DE COLOMBIA) 2010-2012 - Miranda, Dea; Olivia, Yessi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This paper is analysing about counterinsurgency Colombia to against paramilitary group in Colombia to help address the humanitarian crisis that occurred because of civil conflict in Colombia. Conflict in Colombia involving the Fuerzas Armadas Revolucionaries de Colombia (FARC) and the Government of Colombia is one example of a threat to human security in this case is a citizen of Colombia. Thousands of people confirmed dead, and hundreds more injured and displaced into the surrounding area. Colombia has a strategy to fight the Colombian rebel group. Espada de Honor strategy in the fight against the FARC rebel group was born from previous strategies that have not been fully successful in combating the FARC rebel group that Plan Colombia and Plan Patriota. Colombia is a country full of prolonged conflict is filled with murder, brutally massacre, violence, and even abduction by rebel group FARC. This group not only rebel groups in the country have been even this group has turned into an international terrorist views of involvement in illegal drug smuggling.Key Words: Colombia, FARC, Espada De Honor, Drugs, Civil Conflict